Determination and quantification of phytochemicals from the leaf extract of Parthenium hysterophorus L. and their physio-biochemical responses to several crop and weed species - Khairul Bashar, H. M.; Juraimi, Abdul Shukor; Ahmad Hamdani, Muhammad Saiful; Uddin, Md. Kamal; Asib, Norhayu; Anwar, Md. Parvez; Rahaman, Ferdoushi; Rezaul Karim, S. M.; Haque, Mohammad Amdadul; Berahim, Zulkarami; Nik Mustapha, Nik Amelia; Hossain, Akbar (MDPI, 2022)
This current investigation was undertaken both in laboratory and glasshouse for documentation and quantification of phytochemicals from different parts of the parthenium (Parthenium hysterophorus L.) plant through LC-MS and HPLC to study their effect on two crops namely, Bambara groundnut (Vigna subterranean L.) and maize (Zea mays L.), and six different types of weed e.g., Digitaria sanguinalis, Eleusine indica, Ageratum conyzoides, Cyperus iria, Euphorbia hirta, and Cyperus difformis. The parthenium methanolic leaf extracts at 25, 50, 75, and 100 g L−1 were sprayed in the test crops and weeds to assess their physiological and biochemical reactions after 6, 24, 48, and 72 h of spraying these compounds (HAS). The LC-MS analysis confirmed seven types of phytochemicals (caffeic acid, ferulic acid, vanillic acid, parthenin, chlorogenic acid, quinic acid, and p-anisic acid) in the parthenium leaf extract that were responsible for the inhibition of tested crops and weeds. From the HPLC analysis, higher amounts in leaf methanol extracts (40,752.52 ppm) than those of the stem (2664.09 ppm) and flower extracts (30,454.33 ppm) were recorded. Parthenium leaf extract at 100 g L−1 had observed higher phytotoxicity on all weed species except C. difformis. However, all crops were found safe under this dose of extraction. Although both crops were also affected to some extent, they could recover from the stress after a few days. The photosynthetic rate, transpiration rate, stomatal conductance, carotenoid and chlorophyll content were decreased due to the application of parthenium leaf extract. However, when parthenium leaf extract was applied at 100 g L−1 for 72 h, the malondialdehyde (MDA) and proline content were increased in all weeds. Enzymatic antioxidant activity (e.g., superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) contents) were also elevated as a result of the sprayed parthenium leaf extract. The negative impact of physiological and biochemical responses as a consequence of the parthenium leaf extract led the weed species to be stressed and finally killed. The current findings show the feasibility of developing bioherbicide from the methanolic extract of parthenium leaf for controlling weeds, which will be cost-effective, sustainable, and environment friendly for crop production during the future changing climate.